2005
DOI: 10.1200/jco.2005.11.080
|View full text |Cite
|
Sign up to set email alerts
|

Hodgkin's Lymphoma in Elderly Patients: A Comprehensive Retrospective Analysis From the German Hodgkin's Study Group

Abstract: Elderly patients have a poorer risk profile compared with younger HL patients and experience more severe treatment-associated toxicity. Higher mortality during treatment as well as lower dose-intensity are the major factors explaining the poorer overall outcome of elderly HL patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
123
1
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 170 publications
(138 citation statements)
references
References 27 publications
10
123
1
4
Order By: Relevance
“…2,3,6 Currently, it is worth mentioning the new forms of treatment, including targeted therapy and the possibility of bone marrow trans- …”
Section: Discussionmentioning
confidence: 99%
“…2,3,6 Currently, it is worth mentioning the new forms of treatment, including targeted therapy and the possibility of bone marrow trans- …”
Section: Discussionmentioning
confidence: 99%
“…In this study, the recurrence of HL was found to have a significant negative impact on survival. In a more recent report by Engert A et al (Engert, Ballova, Haverkamp, et al, 2005), a comprehensive retrospective analysis from the GHSG data base was performed and yielded poorer outcomes for elderly patients. From 4251 patients, 372 (8.8%) were 60 years or older.…”
Section: Presentation and Prognosismentioning
confidence: 99%
“…54,55 Moreover, cardiovascular, respiratory and/or metabolic co-morbidities are important determinants of the less favorable prognosis of Hodgkin's lymphoma in the elderly. 56,57 The EP defined as elderly patients over 70 years and addressed the question of whether a conventional strategy or a reduced-intensity approach is more appropriate for this category of patients.…”
Section: Treatment Of Elderly Patientsmentioning
confidence: 99%